Modeling of the demand deposits from Moroccan commercialbanks - bellaali, Fatima; bouhadi, Abdelhamid el; benali, Mimoun (The journal of contemporary issues in business and government, 2022)
According to the recent recommendations of the Basel committee, the modeling of the flow of the demand deposits is a major issue in the Asset Liability Management. In the present work, we propose a modeling of the flow of the demand deposits (unpaid accounts) of the Moroccan commercial banks. The data have been extracted from the Bank Al-Maghrib (BAM) in order to liquidate the stable portion of these deposits according to the time that the bank can use to grant loans while minimizing the risk of the transition and liquidity. It is found that the deposits of the clients show no apparent behavior in relation to their demand deposits. This results will permit the bank do not take into account the factor of the short-term interest rate as affecting the available volume of a current accounts.